Catalytic, Enantioselective α‐Alkylation of Azlactones with Nonconjugated Alkenes by Directed Nucleopalladation. (27th February 2019) - Nimmagadda, Sri Krishna; Liu, Mingyu; Karunananda, Malkanthi K.; Gao, De‐Wei; Apolinar, Omar; Chen, Jason S.; Liu, Peng; Engle, Keary M.
Abstract: A palladium(II)‐catalyzed enantioselective α‐alkylation of azlactones with nonconjugated alkenes is described. The reaction employs a chiral BINOL‐derived phosphoric acid as the source of stereoinduction, and a cleavable bidentate directing group appended to the alkene to control the regioselectivity and stabilize the nucleopalladated alkylpalladium(II) intermediate in the catalytic cycle. A wide range of azlactones were found to be compatible under the optimal reaction conditions to afford products bearing α, α‐disubstituted α‐amino‐acid derivatives with high yields and high enantioselectivity. Abstract : Doppelte Wirkung : Die asymmetrische α‐Alkylierung von Azlactonen mit nichtkonjugierten Alkenen wird durch die duale katalytische Wirkung von Pd II und einer chiralen Phosphorsäure erzielt. Die Reaktion ermöglicht einen schnellen Zugang zu quartären α‐Aminosäuren.